Sensitivity of larval and juvenile freshwater mussels (unionidae) to ammonia, chloride, copper, potassium, and selected binary chemical mixtures. (January 2020) - Salerno, J.; Gillis, P.L.; Khan, H.; Burton, E.; Deeth, L.E.; Bennett, C.J.; Sibley, P.K.; Prosser, R.S.
Abstract: In aquatic environments, organisms such as freshwater mussels are likely exposed to complex contaminant mixtures related to industrial, agricultural, and urban activities. With growing interest in understanding the risk that chemical mixtures pose to mussels, this investigation focused on the effects of various waterborne contaminants (ammonia, chloride, copper, and potassium) and selected binary mixtures of these chemicals following a fixed-ratio design to Villosa iris glochidia and juvenile Lampsilis fasciola . In individual exposures, 48-h EC50 values were determined for V. iris glochidia exposed to ammonia chloride (7.4 [95% confidence interval (CI) 6.6–8.2] mg N/L), ammonia sulfate (8.4 [7.6–9.1] mg N/L), copper sulfate (14.2 [12.9–15.4] μg Cu 2+ /L), potassium chloride (12.8 [11.9–13.7] mg K + /L), potassium sulfate (10.1 [8.9–11.2] mg K + /L), and sodium chloride (480.5 [435.5–525.5] mg Cl − /L). The 7-d LC50 values for juvenile L. fasciola were determined for potassium sulfate (45.0 [18.8–71.2] mg K + /L), and sodium chloride (1738.2 [1418.6–2057.8] mg Cl − /L). In Ontario these waterborne contaminants have been reported to co-occur, with concentrations exceeding the EC10 for both life stages at some locations. Data from binary mixture exposures for V. iris glochidia (chloride-ammonia, chloride-copper, and copper-ammonia) and juvenile L. fasciola (chloride-potassium) were analyzed using a regression-based, dose-response mixture analysis modeling framework. Results from the mixture analysis were used to determine if an additive model for mixture toxicity [concentration addition (CA) or independent action (IA)] best described the toxicity of each mixture and if deviation towards dose-ratio (DR) or dose-level (DL) synergism/antagonism (S/A) occurred. For all glochidia binary mixture exposures, CA was the best fit model with DL deviation reported for the chloride-copper mixture and DR deviation reported for the copper-ammonia mixture. Using the model deviation ratio (MDR), the observed toxicity in all three glochidia mixture exposures were adequately described by both CA (mean = 0.71) and IA (mean = 0.97) whereas the juvenile mixture exposure was only adequately described by CA (mean = 0.64; IA mean = 0.05). Graphical abstract: Image 1 Highlights: Toxicity of NH3  > Cu > K > Cl to larval Villosa iris . Toxicity of K > Cl to juvenile Lampsilis fasciola . Toxicity of binary mixtures was best described by additive model. Abstract : With freshwater mussels considered one of the most imperiled groups of organisms globally and highly sensitive to some ubiquitous aquatic contaminants, this investigation focused on the effects that ammonia, chloride, copper, potassium, and selected binary chemical mixtures posed to the early life stages of two at-risk mussel species: Villosa iris and Lampsilis fasciola .